Application of artificial intelligence in digital marketing - Mirjana Marić; Olivera Grljević; Luka Gluščević (Anali Ekonomskog fakulteta u Subotici, 2024)
Contemporary digital technologies have significantly influenced the transformation of marketing activities in companies over the past decade. Artificial intelligence is considered one of the most disruptive modern technologies. Their implementation is the most significant challenge of digital marketing. Artificial intelligence can automate customer service, generate content, and enable targeted ad campaigns. The problem identified by the authors is that smaller companies and entrepreneurs lack the necessary knowledge and understanding of artificial intelligence techniques that could enhance digital marketing strategies. By reviewing current literature, this paper aims to explain the digital marketing strategies and the role and place of various artificial intelligence techniques for their improvement. In line with the defined goal, the paper presents three case studies on industry giants Coca-Cola, Starbucks, and Nike, illustrating successful implementations of artificial intelligence and machine learning techniques in their digital marketing.